Pertanggungjawaban Pidana Terhadap Korban Penyalahguna Narkotika - Nurhakim Nurhakim; Ramlani Lina Sinaulan; Mohamad Ismed (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
The purpose of this research is to analyze the criminal responsibility of narcotics abuse against narcotics criminals, and the factors that influence it. This type of research is empirical juridical, with qualitative research methods. The results of the study authors found that criminal liability for narcotics abuse against perpetrators of criminal acts is based on the applicable laws and regulations, namely the Criminal Procedure Code and Law Number 35 of 2009 concerning Narcotics, where judges in examining and deciding cases can seek medical rehabilitation and social rehabilitation.Keywords: Narcotics; Abuse; Accountability AbstrakTujuan penelitian untuk menganalisis pertanggungjawaban pidana penyalahgunaan narkotika terhadap pelaku tindak pidana narkotika, dan faktor-faktor yang mempengaruhinya. Tipe penelitian ini adalah yuridis empiris, dengan metode penelitian kualitatif. Hasil Penelitian penulis mendapatkan bahwa Pertanggungjawaban pidana penyalahgunaan narkotika terhadap pelaku tindak pidana didasarkan atas peraturan perundangundangan yang berlaku yakni KUHAP serta Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika, dimana hakim dalam memeriksa dan memutus perkara dapat mengupayakan rehabilitasi medis maupun rehabilitasi sosial.Kata Kunci: Narkotika; Penyalahgunaan; Pertanggungjawaban